Assessment of climate change impact and adaptation strategy for millet in the Sudano‑Sahelian region of Niger - Tofa, A.I.; Kamara, A.Y.; Mohamed, A.M.L.; Garba, M.; Souley, A.M.; Salissou, H.; Kapran, B.I.; Abdoulaye, T. (Springer, 2024)
Pearl millet is an important food and fodder crop in West African semi-arid regions. Climate change is projected to have a significant impact on the productivity of the crops in these regions. Adaptation strategies to sustain agricultural production are therefore urgently required to sustain millet productivity. The Decision Support System for Agrotechnology Transfer (DSSAT) CERES-Millet model was used to assess the impact of climate change and adaptation strategies on millet in Niger. Three millet varieties and five sowing windows were evaluated as climate change adaptation strategies. We found that temperature and rainfall will increase in the future relative to baseline conditions. The impact of climate change varied with the agroecological zone (AEZ) with higher yield reduction in the Sahel than in the other AEZs. The yield of early-maturing variety (CHAKTI) is projected to decline by 30–72% in all locations and AEZs under all scenarios. Replacing the reference variety HKP with CHAKTI is projected to reduce yields by 35–39% in the Sudan AEZ, 24–32% in the Sudan Sahel AEZ, and 11–18% in the Sahel AEZs. Conversely, using H80-10GR is expected to improve yields by 0–1%, 2–3%, and 0–2% in the respective AEZs, indicating that H80-10GR can be used along with the reference variety (HKP) under future climate. The optimal sowing window for maximum yields under current conditions is consistently identified as June 15–21 across all AEZs, with yield declining significantly with delayed sowing. Future climate scenarios show different impacts by AEZ and climate scenarios. In Sudan AEZ, early sowing on June 1–14 can improve grain yield under RCP 4.5 but may lead to drastic declines by the end of the century under more severe RCP 8.5 conditions for all varieties. In Sudan-Sahel and Sahel AEZs, the optimal sowing window for all varieties is July 1–7 under all climate scenarios. Our results show that early maturity did not result in yield advantage under climate change.